2007
DOI: 10.1016/j.tcs.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Component refinement and CSC-solving for STG decomposition

Abstract: STGs (Signal Transition Graphs) give a formalism for the description of asynchronous circuits based on Petri nets. To overcome the state explosion problem one may encounter during circuit synthesis, a nondeterministic algorithm for decomposing STGs was suggested by Chu and improved by one of the present authors.Here we study how CSC-solving -which is essential for circuit synthesis -can be combined with decomposition. For this purpose, the correctness definition for decomposition is enhanced with internal sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In this case, the enabling of an input by an internal signal should not be interpreted as a causal but a temporal relation. In [SV07] it was shown that the above correctness notion implies that the STG C in Definition 2.5 is in a sense input proper; in particular, if the solution of a CSC-conflict inserts an internal signal in front of an input, it is not correct in the sense of Definition 2.5. Also, correctness is essentially transitive.…”
Section: Stg Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the enabling of an input by an internal signal should not be interpreted as a causal but a temporal relation. In [SV07] it was shown that the above correctness notion implies that the STG C in Definition 2.5 is in a sense input proper; in particular, if the solution of a CSC-conflict inserts an internal signal in front of an input, it is not correct in the sense of Definition 2.5. Also, correctness is essentially transitive.…”
Section: Stg Decompositionmentioning
confidence: 99%
“…• consist of local transitions only -including t d -such that the later gyroscope refinement of q with a new internal signal ic is input proper according to [SV07], which means that no input will be delayed by ic. Furthermore,…”
Section: Inserting Implicit Places Into a Petri Netmentioning
confidence: 99%
“…In a companion paper [9], it is shown that the components produced by our method are still a correct decomposition of the original specification after such insertions; for this, the correctness definition had to be extended to internal signals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in [4] CSC is used to find sufficient input signals for each component, while our method is guided by the detection of auto-conflicts. Correctness is not proven in [4] -not even formulated -, but this has recently been proved in [9] w.r.t. the extended correctness definition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation